Strongyloides Colitis as a Harmful Mimicker of Inflammatory Bowel Disease - Julio Poveda; Farah El-Sharkawy; Leopoldo R. Arosemena; Monica T. Garcia-Buitrago; Claudia P. Rojas (Case Reports in Pathology)
Autoinfection caused by Strongyloides stercoralis frequently becomes a life-long disease unless it is effectively treated. There is overlapping histomorphology between Strongyloides colitis and inflammatory bowel disease; a low index of suspicion can lead to misdiagnosis and fatal consequences. We present a case of Strongyloides colitis mimicking the clinical and pathologic features of inflammatory bowel disease. A 64-year-old female presented to the emergency department with a four-day history of abdominal pain, diarrhea, and hematochezia. Colonoscopy revealed diffuse inflammation suggestive of inflammatory bowel disease, which led to initiation of 5-aminosalicylic acid and intravenous methylprednisolone. Biopsies of the colon revealed increased lymphoplasmacytic infiltrate of the lamina propria with eosinophilic microabscesses and presence of larvae, consistent with Strongyloides stercoralis. Immunosuppressive medication was halted. The patient ultimately died a few days later. This case emphasizes the importance of identifying the overlapping clinical and pathologic features of Strongyloides colitis and inflammatory bowel disease. A high index of suspicion and recognition of particular histological findings, including eosinophilic microabscesses, aid in the correct diagnosis. Definitive diagnosis is crucial as each disease carries distinct therapeutic implications and outcome.